(3QSGdI aj fSHI GdbWQ Edi GdeMjWs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3aCbhd Ef JhVjM eG PcQg GdTGQM ddeMbb aj gPG GdedH HMjK jQJaY Yfg (B... (3GdGMJLGH hdG jHbi ajg Tc hdG GQJjGH ehbha Ydi EjQGO ebOeGJ (B...s
(3BNQgG (B:s
... (3eY Gfg ZjQ Mbjb HGdEgeGd hdYeQj dbO CaQW GdTGQM GdaGVd aj GdJTfjY Ydi PfHc GdeMbbjf ceG JQi hbO YQaJ HeG PcQfGg Cf JTfjYg efYcS (B.. (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B6\ 102s
(3GdPQjYI (B24 \ 731s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdLZQGajG hGdHdOGfs